Ontologi, Aksiologi, dan Epistemologi Energi Baru Terbarukan Terhadap Smart City: Tinjauan Literatur Sistematis - Alfarid Hendro Yuwono; Syaad Patmanthara; Aripriharta Aripriharta; Triyanna Widiyaningtyas; Nafi Isbadrianingtyas; M Ibrahim Ashari (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The development of digital technology and the Internet of Things (IoT) has transformed the paradigm of urban development towards the concept of a smart city based on data and connectivity. This study analyzes the nature of smart cities through three dimensions of the philosophy of science: ontology, epistemology, and axiology. From an ontological perspective, a smart city is understood as a complex entity consisting of physical, digital, social, and ecological systems that interact with each other to create efficient and adaptive urban governance. Epistemologically, knowledge in a smart city is obtained through the process of collecting, processing, and analyzing data from various IoT devices, sensors, and citizen participation, thereby producing new insights that support evidence-based decision-making (data-driven governance). From an axiological perspective, a smart city has ethical values and goals to improve the quality of life of its citizens, strengthen government transparency, maintain environmental sustainability, and promote inclusive social participation. Thus, this study asserts that the development of a smart city is not only technological but also has a philosophical foundation oriented towards a balance between efficiency, humanity, and sustainability.